Rare bird documentation form for Bohemian Waxwing at Hawkeye Wildlife Management Area in 1984 - Hollis, Richard Juleet al (1984)
Rare bird documentation form for one or two Bohemian Waxwings at Hawkeye Wildlife Management Area in Johnson County, IA on November 11, 1984. Epson - sheet feed